Fusion-expressed CtxB-TcpA-C-CPE improves both systemic and mucosal humoral and T-cell responses against cholera in mice. (August 2021) - Souod, Negar; Kargar, Mohammad; Hoseini, Mohammad Hossein; Jafarinia, Mojtaba
Abstract: Background: Development of an effective oral vaccine against Cholera, a life-threatening dehydrating diarrheal disease, proved to be a challenging task. To improve oral subunit vaccine immunogenicity and to prevent the state of oral tolerance, application of mucosal adjuvants might be a promising approach. In the present study, the CtxB-TcpA-C-CPE fusion was constructed in which CtxB and C-CPE were used as mucosal adjuvants and vaccine delivery system, respectively, to induce mucosal immune responses, and to improve the anti-toxin and anti-colonizing immunity against V. cholera e. Materials & methods: The fusion construct was synthesized, sub-cloned in pQE30 and expressed in E. coli . The three antigen, making the fusion protein, were also separately expressed in E. coli . The recombinant proteins were purified by affinity chromatography using Ni-NTA agarose. Western blot analysis using anti-His antibody was applied to confirm identity of the purified proteins. BALB/c mice were subcutaneously immunized with CtxB, TcpA, C-CPE and the fusion protein CtxB-TcpA-C-CPE separately. The mice were orally immunized (in 3 boosts) by the same vaccine. Mucosal immune response stimulation was evaluated by measuring the levels of intestinal IgA. Systemic immune response was evaluated by measuring total serum IgG, IgG1, IgG2a, IgG2b subclasses, and also IL-4, IL-5, IL-10 and IFN-γ cytokines in spleen cell culture. Results: The recombinant proteins CtxB, TcpA, C-CPE and the fusion protein CtxB-TcpA-C-CPE were expressed in E. coli and highly purified in a single step of chromatography. BALB/c mice immunized with the fusion protein had highest levels of intestinal IgA, serum IgG and IgG subclasses, compared to each of the three proteins making the fusion. Moreover, stimulated splenocytes of mice immunized with the fusion protein displayed significantly higher amounts of IL-5 and IFN-ɣ cytokines. Th2 dominance of the immune response was more evident in mice receiving the fusion protein. Conclusion: Inclusion of CtxB, as the mucosal adjuvant, and C-CPE, as the vaccine delivery system, in the fusion protein CtxB-TcpA-C-CPE significantly enhanced the elicited mucosal and systemic immune responses, compared to TcpA alone . Of note, significant production of intestinal IgA in mice immunized with the fusion protein is presumably capable of neutralizing TcpA, CtxB and C-CPE antigens, preventing V. cholera colonization, and toxic function of CtxB and C-CPE. Challenge infection of the immunized mice is required to evaluate protective potential of the fusion protein against V. cholera. Highlights: A new fusion protein consisted of two vibrio cholera virulence factores were constructed as a candidate for a oral vaccine. CtxB and C-CPE were applied as mucosal adjuvants and vaccine delivery system, respectively. The levels of intestinal IgA, Total serum IgG, IgG1, IgG2a, IgG2b subclasses, and also IL-4, IL-5, IL-10 and IFN-γ cytokines in spleen cell culture was measured. The construct of TcpA along with CtxB and C-CPE could make the synergistic effects of these proteins to induce the immune system of the host effectively.